Gastrodin attenuates angiotensin II-induced vascular contraction and MLCK/p-MLC2 pathway activation - Zhi Guo; Xuan Yang; Meizhu Wu; Aling Shen; Jiapeng Li; Xiuli Zhang; Ying Cheng; Qiurong Xie; Jun Peng (Taylor & Francis Group, 2023)
AbstractContext Gastrodin has been used as antihypertension therapy in China; however, the mechanisms underlying the effects of gastrodin have yet to be fully elucidated.Objective To explore the therapeutic efficiency of gastrodin as an antihypertensive and determine the mechanisms underlying this effect.Materials and methods C57BL/6 mice were continuously administered angiotensin II (Ang II) (500 ng/kg/min) to induce hypertension. Mice were randomly divided into control, Ang II and Ang II + gastrodin groups. Mice received intragastric administration of gastrodin (5 mg/kg) or double distilled water once a day for 4 weeks. Blood pressure, pulse wave velocity (PWV), thickness of the abdominal aorta, pathological morphology and differential expression transcripts (DETs) were assessed. Abdominal aorta rings and primary isolated vascular smooth muscle cells were subjected to Ang II stimulation to induce hypertension as ex vivo and in vitro models, respectively. Vascular ring tension, release of Ca2+ and levels of proteins involved in the myosin light chain kinase (MLCK)/phospho-myosin light chain 2 (p-MLC2) pathway were determined.Results Gastrodin treatment attenuated increases in blood pressure, PWV and thickness of the abdominal aorta. Treatment with gastrodin resulted in 2785 DETs and the enrichment of vascular contraction and calcium signalling pathways. Gastrodin treatment attenuated Ang II-induced vasoconstriction, produced a norepinephrine-precontracted vasodilation effect (attenuated by verapamil), and reduced intracellular Ca2+ release. Furthermore, gastrodin suppressed activation of the MLCK/p-MLC2 pathway in vivo and in vitro.Conclusions Gastrodin treatment lowers blood pressure, suppresses Ang II-induced vascular contraction and MLCK/p-MLC2 pathway activation, thereby demonstrating the mechanisms underlying the therapeutic efficacy of gastrodin as an antihypertensive.